Quiet and perturbed ionospheric representation according to the electron content from GPS signals - Brunini, Claudio Antonio (2003)
Signals from Global Positioning System (GPS) satellites received at the surface of the Earth have passed through the terrestrial atmosphere and are therefore affected by refraction in the ionosphere. A large number of permanent dual frequencies GPS tracking stations have been built up in the last years and their data have proved to be suitable to study the ionosphere. The main goal of this paper is to assess the capability of these observations to continuously and routinely monitor the ionosphere at a global scale. The interest was focused on retrieving the coefficients of a spherical harmonics expansion that describe the global distribution of the vertical total electron content (VTEC) from the GPS signal. To test our results, we compare them with other GPS-derived results, with VTEC values computed with the International Reference Ionosphere (IRI-95) model, and with direct VTEC determinations provided by Topex-Poseidon satellite. A large set of global VTEC maps with a time resolution of 2 hours was used to describe the evolution of this ionospheric variable at quiet geomagnetic periods during the year 1997. The outstanding features of the VTEC during the 15 May 1997 geomagnetic storm have also been studied. The results show that our method is able to identify large-scale features and seasonal variations of the VTEC in quiet conditions, as well as its variations during a large geomagnetic storm.